Elastic fracture mechanics analysis of bi-materials using boundary element method - Tan, Benjamin Zi Ming (Nanyang Technological University, 2020)
The fracture and stress analysis for central cracks and diagonally apart cracks in an interface between two dissimilar isotropic elastic half planes were analysed. The analysis was subjected to tensile loading, perpendicular to the crack, on the material. The stress intensity factors (SIF) were calculated, with varying elastic properties, for the different models. The boundary element method (BEM) was used in this study, together with the quadratic quarter-point crack tip elements. It was discovered that when distance between two cracks on the same and different interface yielded different results on the stress intensity factors.